On Board the Titanic - Tanaka, Shelley (USA, 1996)
Seventeen-year-old Jack Thayer explores the Titanic and forms a brief freindship with another passenger before experiencing the wreck of the giant ocean liner...
Keywords: Adventure; Historical Fiction -Titanic (Steamship); Juvenile Fiction; Shipwreck - Ocean Liner